2022
DOI: 10.25251/skin.6.6.3
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated 31-Gene Expression Profile (i31-GEP) Test for Cutaneous Melanoma Outperforms a Clinicopathologic-only Nomogram at Identifying Patients who can Forego Sentinel Lymph Node Biopsy

Abstract: Introduction: National guidelines for cutaneous melanoma suggest avoiding sentinel lymph node biopsy (SLNB) if the risk of SLN positivity is <5% (T1a with no high-risk features), considering SLNB if the risk is 5-10% (T1a with additional high-risk features (T1aHR) and T1b), and offering SLNB if the risk is >10% (T2-T4). Because most patients (88%) who undergo an SLNB have a negative result, novel tools to identify patients who can safely forgo SLNB are critical. The integrated 31-gene expression profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…After screening the articles, 32 met inclusion criteria and were distributed to the panelists for review prior to the roundtable discussion. Of these articles, the number of papers that specifically studied the validity, accuracy, or clinical utility of each test was: 22 for the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , 2 for the 11-GEP test 11,34 , and 7 for the 8-GEP + CP test. 5,13,23,[43][44][45][46]…”
Section: Comprehensive Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…After screening the articles, 32 met inclusion criteria and were distributed to the panelists for review prior to the roundtable discussion. Of these articles, the number of papers that specifically studied the validity, accuracy, or clinical utility of each test was: 22 for the 31-GEP test 4,[19][20][21][22][23][24][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42] , 2 for the 11-GEP test 11,34 , and 7 for the 8-GEP + CP test. 5,13,23,[43][44][45][46]…”
Section: Comprehensive Literature Searchmentioning
confidence: 99%
“…48 While sentinel lymph node positivity is a key prognostic marker, studies have shown that < 20% of patients who undergo the biopsy are found to have nodal metastasis. 50 Given that the procedure has a > 10% risk of complications such as bleeding, infection, pain, neuropathy, lymphocele, lymphatic fistula, and lymphedema 4 , identifying patients that can safely forego the biopsy can significantly reduce morbidity. A multi-center validation study of the i-31 GEP test (a test that integrates the 31-GEP with clinicopathological features including Breslow thickness, mitotic rate, ulceration status, and patient age) showed that the test increased the proportion of patients with T1-T4 tumors predicted to have <5% risk of SLNB positivity from 8.5% to 27.7% with a negative predictive value (NPV) of 98%.…”
Section: Consensus Recommendationsmentioning
confidence: 99%
See 3 more Smart Citations